Означення та використання множини строго раціональних стратегій у деяких антагоністичних іграх - Романюк, В.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
There has been defined the set of strictly rational strategies and the set of
nonstrictly rational strategies of a player in the antagonistic game. On the example it
has been shown what advantage a player obtains if it applies the set of strictly rational
strategies by the other player swerve from the set of its optimal strategies.